Biochemical Changes Associated with Using Overdose of Tramadol in Liver Enzymes of Rabbits. (Journal of Hama University, 2022)
The research was conducted on (24) male rabbits, aged between (6-4 ) months , and an average weight between ( 800-1200 ) G, obtained from local markets in Hama province, in order to study the histological changes associated with the use of Tramadol overdoses on liver and kidney tissue in rabbits .The experimental animals were placed in the barn of the research unit of the Faculty of Veterinary Medicine for 15 days to adapt, then randomly divided into (4) groups where each group included ( 6 ) rabbits .The first group ( control group) was given only a balanced diet and was left until the end of the trial period ( 28 days), while the second group was given Tramadol intramuscularly at a dose of 40 mg/kg per day until the end of the trial period, the third group was given Tramadol intramuscularly at a dose of 50 mg/kg per day until the end of the trial period, and the fourth group was given Tramadol intramuscularly at a dose of 60 mg/kg per day throughout the trial period .Blood samples were collected twice from the collections of the experiment, and the first collection after the end of the first day, third blood sample collected at the end of the experiment ( 28 days ), and then conducted an analysis appropriate to address the levels of activity of enzymes of hepatic transaminase Secretary aminotransferase Alanine aminotransferase ( ALT) In addition to the tanker Amin aspartate aminotransferase Aspartate aminotransferase ( AST ) and measure the level of creatinine ( Creatinine )The macroscopic changes in liver and kidney tissue were recorded in rabbits, and then samples were taken from these livers and kidneys, placed in 10% neutral formalin, then the samples were subjected to wax insertion and prepared tissue sections with a thickness of ( 4-6 ) microns, and the tissue sections were dyed with hematoxylin and eosin to study the resulting microscopic changes .Results of the study showed the existence of differences significant (P
Keywords: Biochemical Changes; Tramadol; Enzymes; Liver; Rabbits